Amerindian ancestry influences genetic susceptibility to chronic obstructive pulmonary disease - Díaz-Peña, Roberto; Boekstegers, Felix; Silva, Rafael S.; Jaime, Sergio; Hosgood, H. Dean; Miravitlles, Marc; Agustí, Àlvar; Lorenzo Bermejo, Justo; Olloquequi, Jordi (Journal of Personalized Medicine, 2020)
The contribution of genetic ancestry on chronic obstructive pulmonary disease (COPD) predisposition remains unclear. To explore this relationship, we analyzed the associations between 754,159 single nucleotide polymorphisms (SNPs) and risk of COPD (n = 214 cases, 193 healthy controls) in Talca, Chile, considering the genetic ancestry and established risk factors. The proportion of Mapuche ancestry (PMA) was based on a panel of 45 Mapuche reference individuals. Five PRDM15 SNPs and two PPP1R12B SNPs were associate with COPD risk (p = 0.05 to 5 × 10−4) in those individuals with lower PMA. Based on linkage disequilibrium and sliding window analyses, an adjacent PRDM15 SNPs were associated with COPD risk in the lower PMA group (p = 10−3 to 3.77 × 10−8). Our study is the first to report an association between PPP1R12B and COPD risk, as well as effect modification between ethnicity and PRDM15 SNPs in determining COPD risk. Our results are biologically plausible given that PPP1R12B and PRDM15 are involved in immune dysfunction and autoimmunity, providing mechanistic evidence for COPD pathogenesis and highlighting the importance to conduct more genome wide association studies (GWAS) in admixed populations with Amerindian descent.